Reduced Frequency of Memory T Cells and Increased Th17 Responses in Patients with Active Tuberculosis (2012)
ABSTRACT: Phenotypic and functional alterations in Mycobacterium tuberculosis T cell subsets have been reported in patients with active tuberculosis. A better understanding of these alterations will increase the knowledge about immune-pathogenesis and also may contribute to the development of new diagnostics and prophylactic strategies. Here, the ex vivo phenotype of CD4 and CD8 T cells and the frequency and phenotype of gamma interferon (IFN-)- and interleukin 17 (IL-17)-producing cells elicited in short-term and long-term cultures following CFP-10 and purified protein derivative (PPD) stimulation were determined in non-infected persons (non-TBi), latently infected persons (LTBi), and patients with active tuberculosis (ATB). Phenotypic characterization of T cells was done based on the expression of CD45RO and CD27. Results show that ATB had a reduced frequency of circulating CD4 CD45RO CD27 T cells and an increased frequency of CD4 CD45RO CD27 T cells. ATB also had a higher frequency of circulating IL-17-producing CD4 T cells than did LTBi after PPD stimulation, whereas LTBi had more IFN- -producing CD4 T cells than did non-TBi. The phenotype of IFN--producing cells at 24 h differs from the phenotype of IL17-producing cells with no differences between LTBi and ATB. At 144 h, IFN-- and IL-17-producing cells were mainly CD45RO CD27 T cells and they were more frequent in ATB. These results suggest that M. tuberculosis infection induces alterations in T cells which interfere with an adequate specific immune response.